Synthesis and Characterization of Mixed Ligand Complexes of Dioxouranium(VI) with Isatin-3-semicarbazone - ABHILASHA, A.; SOBHANA, D. (Asian Journal of Chemistry, 2010)
Some dioxouranium(VI) complexes have been synthesized with the Schiff base derived from indole-2,3-dione (isatin) and semicarbazone. Anions such as acetate, lactate, nitrate, perchlorate, sulphate and thiocyanate act as secondary ligands coordinating to the metal ion. Mixed ligand complexes with dimethyl sulphoxide or diphenyl thiourea and isatin-3-semicarbazone have also been synthesized. Physico-chemical properties of the complexes have been investigated by spectral analyses, molar conductance, molar mass determination and thermal analyses.